2019
DOI: 10.3390/ijms20122941
|View full text |Cite
|
Sign up to set email alerts
|

MtBZR1 Plays an Important Role in Nodule Development in Medicago truncatula

Abstract: Brassinosteroid (BR) is an essential hormone in plant growth and development. The BR signaling pathway was extensively studied, in which BRASSINAZOLE RESISTANT 1 (BZR1) functions as a key regulator. Here, we carried out a functional study of the homolog of BZR1 in Medicago truncatula R108, whose expression was induced in nodules upon Sinorhizobium meliloti 1021 inoculation. We identified a loss-of-function mutant mtbzr1-1 and generated 35S:MtBZR1 transgenic lines for further analysis at the genetic level. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Due to the widespread distribution of receptor BRI1 and key transcription factor BZR1 in roots (Fig. S11), BR regulates a wide range of root growth and developmental processes, including the root cell elongation, root hair formation, lateral root initiation, nodulation in legume species, maintenance of meristem size, and promotion of QC cell division (Bao et al ., 2004; Ferguson et al ., 2005; Terakado et al ., 2005; Kuppusamy et al ., 2009; Gonzalez‐Garcia et al ., 2011; Hacham et al ., 2011; Bergonci et al ., 2014; Fridman et al ., 2014; Chaiwanon & Wang, 2015; Gupta et al ., 2015; Cui et al ., 2019). Here, we further showed that BR plays critical roles for the maturation of ground tissue through regulating the timing and extent of periclinal cell division.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the widespread distribution of receptor BRI1 and key transcription factor BZR1 in roots (Fig. S11), BR regulates a wide range of root growth and developmental processes, including the root cell elongation, root hair formation, lateral root initiation, nodulation in legume species, maintenance of meristem size, and promotion of QC cell division (Bao et al ., 2004; Ferguson et al ., 2005; Terakado et al ., 2005; Kuppusamy et al ., 2009; Gonzalez‐Garcia et al ., 2011; Hacham et al ., 2011; Bergonci et al ., 2014; Fridman et al ., 2014; Chaiwanon & Wang, 2015; Gupta et al ., 2015; Cui et al ., 2019). Here, we further showed that BR plays critical roles for the maturation of ground tissue through regulating the timing and extent of periclinal cell division.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic analyses have identified a large number of transporter-encoding genes that are induced in nodules (Colebatch et al, 2004;Takanashi et al, 2012;Laloum et al, 2014). This includes NPF and NRT2 genes (Criscuolo et al, 2012;Clarke et al, 2015) although the role of these proteins in nodule functioning has been reported only for a few of the family members.…”
Section: Transporters In Symbiotic Nitrogen Fixationmentioning
confidence: 99%
“…However, the regulatory mechanisms remain largely unknown. In plants, there are two families of transporters for NO 3 − transport, a large NPF/NRT1 family of mostly low-affinity transporters (>80 members in L. japonicus and M. truncatula), and a small NRT2 family of high-affinity NO 3 − transporters (<5 in L. japonicus and M. truncatula; Criscuolo et al, 2012;Sol et al, 2019). The high-affinity LjNRT2.4 protein expressed in root and nodule vascular tissues has been identified to play a positive role in the regulation of nodule development and function by a low level of NO 3 − , supporting a NO 3 − -NO cycle being an alternative energy source for mitochondria and bacteroids and this is particularly important for symbiotic N fixation under a A B FIGURE 3 | An overview of symbiotic signaling under high NO 3 − and Pi deficiency in legumes.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Circadian and dial regulation of the levels of phytohormones is widespread in plants, likely involving a complex network of hormone signaling pathways. Circadian oscillations in the major growth-related phytohormones, including ethylene (ET), auxin/indole-3-acetic acid proteins (Aux/IAAs), cytokinins (CKs), gibberellins (GAs), and brassinosteroids (BRs), have been studied in multiple species that demonstrated species- and/or tissue-specific variations [ 30 , 31 , 32 , 33 , 34 , 35 ]. It is worth noting that defense-related hormones such as jasmonic acid (JA) and salicylic acid (SA) also undergo circadian oscillations.…”
Section: Defining the Important Components Of Clock Researchmentioning
confidence: 99%